Oil-cooled transformer hot spot temperature reduction using windings height optimum design - Mohammad Ali Taghikhani (International Journal of Thermofluids)
Transformers are used in transmission and distribution of electrical energy in the power network. Thus, electrical and physical optimization of transformers are important. On the other hand, estimation of the temperature rise and reduction of the hot spot temperature (HST) in a transformer increase the loading capability and life span of the transformer. In this paper, characteristics of an oil-immersed transformer is optimized and minimum losses of the transformer is calculated. For this purpose, the meta-heuristic modified Arctic Puffins optimization (MAPO) algorithm is used to optimize the transformer design. Moreover, temperature distribution in the transformer windings are simulated in different load conditions using a numerical method based on heat transfer theory and heat conduction equation. Besides, the effects of the transformer winding dimensions on the HST are investigated in different load conditions. The results show that the HST value in the windings is minimized at a specific height of the windings. Furthermore, the proposed method for the HST estimation seems to correspond with the results of FEM modeling and measurements in the previous works.